Antimicrobial Dispensing Practices during COVID-19 and the Implications for Pakistan - Bushra Gul; Maria Sana; Aneela Saleem; Zia Ul Mustafa; Muhammad Salman; Yusra Habib Khan; Tauqeer Hussain Mallhi; Tiyani Milta Sono; Johanna C. Meyer; Brian B. Godman (MDPI AG, 2023)
Antibiotics are one of the most frequently dispensed classes of medicines. However, excessive misuse and abuse enhances antimicrobial resistance (AMR). Previous studies in Pakistan have documented extensive dispensing of 'Watch' and 'Reserve' antibiotics, which is a concern. In view of this, there is a need to assess current dispensing patterns following COVID-19 in Pakistan. A cross-sectional study was undertaken, collecting dispensing data from 39 pharmacies and 53 drug stores from November 2022 to February 2023. Outlets were principally in urban areas (60.9%), with pharmacists/pharmacy technicians present in 32.6% of outlets. In total, 11,092 prescriptions were analyzed; 67.1% of patients were supplied at least one antimicrobial, 74.3% antibiotics, 10.2% antifungals and 7.9% anthelmintics. A total of 33.2% of antimicrobials were supplied without a prescription. Common indications for dispensed antibiotics were respiratory (34.3%) and gastrointestinal (16.8%) infections, which can be self-limiting. In addition, 12% of antibiotics were dispensed for the prevention or treatment of COVID-19. The most frequent antibiotics dispensed were ceftriaxone (18.4%) and amoxicillin (15.4%). Overall, 59.2% antibiotics were 'Watch' antibiotics, followed by 'Access' (40.3%) and 'Reserve' (0.5%) antibiotics. Of the total antibiotics dispensed for treating COVID-19, 68.3% were 'Watch' and 31.7% 'Access'. Overall, there appeared to be an appreciable number of antibiotics dispensed during the recent pandemic, including for patients with COVID-19, alongside generally extensive dispensing of 'Watch' antibiotics. This needs to be urgently addressed with appropriate programs among pharmacists/pharmacy technicians to reduce AMR.